Two new species of Myotis (Chiroptera: Vespertilionidae) for Argentina - Barquez, Rubén M. (2017)
Seven new species of Myotis have been recently described from South America, elevating to 20 the total number of species of the genus recognized for the region. Myotis izecksohni and Myotis lavali were recently described from the States of Río de Janeiro, Paraná and Pernambuco, Brazil. These are clearly different from all other known species of the genus in their external and cranial characters, which are exactly comparable with our specimens collected in Argentina. This allows to greatly expand the known geographic distributions for these two species. The addition to Argentina of Myotis lavali with specimens collected in the Yungas ecoregion of Salta Province, and Myotis izecksohni with specimens collected in the Fields and Weedlands ecoregion of Misiones Province, increases the known ecoregions to date for the distribution of the two species.